PENGARUH REPUTASI TERHADAP LOYALITAS NASABAH DI BPRS SUKOWATI SRAGEN - Aulia Nur Rahmasari; Rofiul Wahyudi (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2020)
BPRS Sukowati Sragen is one of the regional companies that has a good reputation as evidenced by various awards from stakeholders.This research aims to find out the influence of reputation on customer loyalty in BPRS Sukowati Sragen.Â This study uses quantitative approaches through google form questionnaires and populations in this study using BPRS customer Sukowati Sragen. The study used sample determination techniques with snowball sampling and analysis in this study using simple regression analysis with SPSS analysis tool version 2.0.The results of this study reputation have a significant influence on customer loyalty at BPRS Sukowati Sragen. This is evidenced reputation has a significant rate of 92% to customer loyalty. While 8% is likely to be influenced by product quality, customer satisfaction or customer trust. Researchers did not examine 8% of these other factors.